2004
DOI: 10.1093/nar/gkh317
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of Srs2 in post-replication repair and homologous recombination in fission yeast

Abstract: Homologous recombination is important for the repair of double-strand breaks and daughter strand gaps, and also helps restart stalled and collapsed replication forks. However, sometimes recombination is inappropriate and can have deleterious consequences. To temper recombination, cells have employed DNA helicases that unwind joint DNA molecules and/or dissociate recombinases from DNA. Budding yeast Srs2 is one such helicase. It can act by dissociating Rad51 nucleoprotein filaments, and is required for channell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 53 publications
11
70
0
Order By: Relevance
“…Therefore, we began our investigation of the meiotic roles of Rqh1 by examining the effect of an rqh1 null mutation (a complete deletion of the rqh1 coding sequence) on meiotic recombination frequency. In addition, we examined the effect of an srs2 null mutation because of the known interaction between Rqh1 (Sgs1) and Srs2 in mitotic growth and the role of both Rqh1 (Sgs1) and Srs2 proteins in promoting mitotic noncrossover vs. crossover events (Gangloff et al 2000;Maftahi et al 2002;Ira et al 2003;Doe and Whitby 2004;Liberi et al 2005;Hope et al 2007;J. Virgin, personal communication).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we began our investigation of the meiotic roles of Rqh1 by examining the effect of an rqh1 null mutation (a complete deletion of the rqh1 coding sequence) on meiotic recombination frequency. In addition, we examined the effect of an srs2 null mutation because of the known interaction between Rqh1 (Sgs1) and Srs2 in mitotic growth and the role of both Rqh1 (Sgs1) and Srs2 proteins in promoting mitotic noncrossover vs. crossover events (Gangloff et al 2000;Maftahi et al 2002;Ira et al 2003;Doe and Whitby 2004;Liberi et al 2005;Hope et al 2007;J. Virgin, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…The function of Srs2 often seems to be closely linked to that of Sgs1 or Rqh1. Both Sgs1 (Rqh1) and Srs2 proteins have an antirecombination function during mitotic growth of budding and fission yeast (Rong et al 1991;Watt et al 1996;Stewart et al 1997;Wang et al 2001;Doe and Whitby 2004;J. Virgin, personal communication).…”
mentioning
confidence: 99%
“…However, Mus81 and Rad54 are not obligatory functional partners: Whereas Mus81 Ϫ/Ϫ ES cells are hypersensitive to hydroxyurea, Rad54 Ϫ/Ϫ ES cells are not (38). Also, in S. pombe, Mus81 and Rad54 likely act in parallel but distinct pathways of DNA repair because mus81rad54 double mutant has severely reduced viability (39). However, poor growth and hypersensitivity of S. pombe mus81rad54 double mutants to genotoxic agents is suppressed by loss of upstream proteins, such as Rad51 and Rad55 (40), indicating a link between the function of these 2 proteins and HR.…”
Section: Discussionmentioning
confidence: 99%
“…This recombination may be necessary in some cases to complete replication and maintain viability, but a number of studies have suggested that recombination proteins may also target stalled forks and initiate exchanges when there is no need. They may even cause harm by provoking unequal exchanges between repeated sequences (Rothstein et al 2000;Fabre et al 2002;Doe and Whitby 2004;Schmidt and Kolodner 2004). Faithful duplication of the genome may rely therefore not only on the ability to minimize impediments to fork progression and to rescue any forks that have been damaged, but also to limit unnecessary recombination.…”
mentioning
confidence: 99%